Cambridge English. First Result student's book - Davies P. A. Paul (Oxford, Oxford University Press, 2019)
This popular and successful course has been revised and updated to reflect the requirements of the 2015 Cambridge English: First (FCE) exam. Practice tasks for all parts of the exam provide complete support. Vibrant, contemporary design with high-impact visuals keeps motivation high. Crammar and vocabulary tasks develop language skills. Writing guide with sample answers provides extra writing practice. Also available to use with this course:Cambridge English: First Online Practice. skills training and additional exam practice online. automatic marking and explanatory feedback on answers. speak-and-record activities.